KEANEKARAGAMAN JENIS DAN SEBARAN IKAN PADA EKOSISTEM TERUMBU KARANG DI TAMAN NASIONAL KEPULAUAN SERIBU - , SETYADI; , Dr. Ir. Djumanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Coral reef fishes utilize coral reef as a nursery ground, feeding ground, spawning ground and refuge from predator, so there is a relationship between coral reefs and coral reef fishes. The purpose of the study was to determine the fishes diversity and dominant distribution of coral reef fishes in Kepulauan Seribu National Park. The study was done on May 8th-16th 2013 in the waters of the Kepulauan Seribu National Park. There were 20 stations for observation which each station was located closed to islands in management zone of Kepulauan Seribu National Park. Coral reef fishes were observed twice at a depth of 9 meter using Underwater Visual Census ( UVC ) with a 50 meter long transect and covered 2.5 meter both side of the transect line. Reef fish species were identified directly in situ. Measurement of environmental parameters were done in situ with 3 replicates. Collected data were analyzed descriptively for species of coral reef fishes, fishes dominant, fishes composition by zoning, and other used biological indices namely are fish diversity index, evenness index, dominance index (D) and abundance index (X). The result showed there was 13473 individualtis comprise of 171 species and 31 families. The dominant species with more of 10% percentage total were Caesio cuning (18,07%), Cirrhilabrus cyanopleura (13,62%) and Chromis fumea (11,69%). Distribution of dominant fish namely Cirrhilabrus cyanopleura and Caesio cuning concentrated in the eastern part of the National Park with the center point spread apart. The distribution of dominant fish namely Chromis fumea was spread out almost evenly among area with the highest in the northern part. The diversity index (H) was ranged from 2.33 to 3.65, evenness index (E), between 0.38 to 0.60 and dominance index (D) ranged between 0.04 to 0.20. The abundance index (X) was ranged from 0.70 to 7.44 ind/m2. The major fish species were dominance among stations. The number of Caesio cuning was dominance and the greatest. The diversity of coral reef fish classified as moderate to high. Environmental parameters were relatively in good condition and suitable for fishes.